School Policy and Teacher Competency to Prepare Literacy Teaching Materials for Early Children Based on Local Stories - Yakin, Wilda Fitria; Maskud; Madi, Faisol Nasar bin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This article describes school policies and teacher competencies for preparing literacy teaching materials for early childhood based on local stories at Madrasah Ibtidaiah Negeri 02 Situbondo, East Java. The research method used is a qualitative approach with a case study approach. Data was collected through unstructured interviews, observation, and documentation of relevant archives. The subjects of this research were students, facilitators, and heads of Madrasah Ibtidaiah Negeri 02 Situbondo. The data analysis technique used in this research is the Miles and Huberman data analysis model: data condensation, data display, and conclusion drawing/verification. The research results show that the policy of integrating religious literacy and Arabic literacy in MIN 02 is based on Minister of Education and Culture Regulation No. 23 of 2015 concerning growing interest in reading, outlined in the school's vision, mission, and literacy guidebook. Each class creates an assessment book the teacher uses to assess students' religious literacy and Arabic language skills. They were handed over to parents at the end of each semester. The role of teacher competence in developing Arabic language teaching materials used by Madrasah Ibtidaiah Negeri 02 Sitobondo teachers includes needs analysis through field studies and literature studies regarding regional song sagas about Situbondo. Meanwhile, the design of teaching materials uses the Canva application. They were followed by the testing phase of teaching materials and revision of teaching materials.